Individual psychological security in the post-isolation period as a scientific research subject (Revista de Investigaciones Universidad del Quindío, 2022)
The psychological security of a person is an indicator of a person who is psychologically healthy and able to cope with social, pandemic, informational, psychological, and other threats. The sudden spread of a new type of coronavirus infection, COVID-19, since December 2019 has significantly destabilized society. This study aims to investigate and analyze individual psychological security as a scientific research subject in the post-isolation period. To fulfill that aim, a range of scientifical methods are employed, including analysis and synthesis of scientific content on the issues under study, sociometry method, summary, and grouping of statistical observation materials. Given the results, it can be concluded that the swift spreading of mass hysteria and panic resulting from COVID-19 has been characterized by constant psychological issues in public, consisting of a decline in the level of psychological safety. That factor seems to be associated with the coping strategies adopted, the level of conscious awareness, socio-demographic variables, people’s habits, and how an individual utilizes media and interprets information.
Keywords: psychological safety; personality; post-isolation period; COVID-19; psychosocial impacts